2021
DOI: 10.3389/fimmu.2021.732693
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Epitope Abundance Supports Vaccine-Induced Cytotoxic Protection Against SARS-CoV-2 Variants of Concern

Abstract: The effect of emerging SARS-CoV-2 variants on vaccine efficacy is of critical importance. In this study, the potential impact of mutations that facilitate escape from the cytotoxic cellular immune response in these new virus variants for the 551 most abundant HLA class I alleles was analyzed. Computational prediction showed that most of these alleles, that cover >90% of the population, contain enough epitopes without escape mutations in the principal SARS-CoV-2 variants. These data suggest that the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Therefore, first bioinformatics prediction to the theoretical epitopes from the SARS-CoV-2 spike protein, the viral protein included in internationally licensed vaccines, was carried out as previously described [ 15 , 16 ]. Each of the 551 HLA class I alleles associated with the twelve canonical HLA-A and -B class I supertypes were analyzed, respectively ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, first bioinformatics prediction to the theoretical epitopes from the SARS-CoV-2 spike protein, the viral protein included in internationally licensed vaccines, was carried out as previously described [ 15 , 16 ]. Each of the 551 HLA class I alleles associated with the twelve canonical HLA-A and -B class I supertypes were analyzed, respectively ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the real scenario analyzed in the current study, the 30 changes, 3 deletions, and 1 insertion generated by the Omicron variant of concern versus current SARS-CoV-2 vaccines, only with the A03 supertype was a similar (26%) escape mutation rate found. A02 was the second supertype affected (21%), while in the other 10 HLA class I supertypes, this rate was less than 20%, resulting in a 12% escape mutation rate on average for the 12 HLA class I supertypes analyzed, less than half of the theoretical rate calculated by random mutation (12). B58, with only 2% altered epitopes, and B08 without predicted epitopes modified in Omicron strain versus SARS-CoV-2 vaccines were the HLA class I supertypes least impacted by the Omicron variant of concern.…”
Section: Resultsmentioning
confidence: 84%
“…In our previous study about the effect of emerging SARS-CoV-2 variants identified to May 2021 on cytotoxic T-cell response generated by the licensed vaccines, a prediction of the number of intact epitopes for some representative alleles of the twelve HLA class I supertypes was calculated after random progressive position sets ranging from the length of the full spike protein (12). In this hypothetical scenario, 39 random mutations in the spike protein sequence did not prevent the fact that the 75% of predicted cytotoxic epitopes derived from SARS-CoV-2 vaccines remained unaltered (12). In the real scenario analyzed in the current study, the 30 changes, 3 deletions, and 1 insertion generated by the Omicron variant of concern versus current SARS-CoV-2 vaccines, only with the A03 supertype was a similar (26%) escape mutation rate found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a subtractive approach, we identified 34 unique proteins via infected patient sera, in both membranous and secretome of A. baumannii. Majority of those proteins were not deeply analyzed with classical approaches or in silico and was somehow disregarded as potential vaccine candidate (e.g., B0V885 / ABAYE3068) [21,25,26]. Taking into consideration of structure, transmembrane properties, epitope regions and solubility of identified proteins, we further analyzed nine of them as potential recombinant vaccine candidate.…”
Section: Epitope Alignment To Protein Structurementioning
confidence: 99%